Improvement in left atrial reservoir strain following hematopoietic stem cell transplant in patients with systemic sclerosis. (8th February 2021) - Chen, C; Nishtala, A; Groenendyk, JW; Schultz, W; Li, E; Shah, SJ; Burt, RK; Freed, BH
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Systemic sclerosis (SSc) can cause cardiac complications as a result of multi-organ fibrosis. The study of left atrial (LA) mechanics can offer insights into the pathophysiology of cardiac involvement in SSc. LA strain measured by speckle-tracking echocardiography (STE) has been shown to be a sensitive marker of LA function. The impact of a disease modifying treatment like hematopoietic stem cell transplant (HSCT) on LA mechanics is not known. Aim: To study the effect of HSCT on LA mechanics using both conventional echocardiography and STE. Methods: Patients with SSc who underwent comprehensive 2D echo evaluation pre- and post-HSCT were identified. Patients with pulmonary hypertension on right heart catheterization (RHC) were excluded. The modified Rodnan skin score (mRSS) was evaluated for each patient pre- and post-HSCT. Speckle tracking software was utilized to measure myocardial strain (TomTec, Unterschleissheim, Germany). LA reservoir strain was measured from the apical 2-, and 4-chamber views. The ratio of E/e' to LA reservoir strain was used to non-invasively estimate LA stiffness. Paired student's t-test and Pearson"s correlation were used in data analysis. Results: Among 89 patients with SSc (average age 46 ± 11 years, 75% female) who underwent HSCT, the mRSS significantly improved after HSCT. The mean pulmonary capillary wedge pressure (PCWP) measured by RHC prior to HSCT was 9.6 ± 4.1 mmHg. LA reservoir strain was abnormal at baseline and significantly improved following HSCT. Although LA volume index and E/e' remained unchanged, LA stiffness index decreased significantly post-HSCT. There was no correlation between LA reservoir strain and PCWP at baseline or between change in LA reservoir strain and change in LA volume index or E/e'. Conclusions: Patients undergoing HSCT for SSc show significant improvement in LA reservoir strain and LA stiffness despite no significant change in LA volumes or estimates of LV filling pressures. This improvement in LA mechanics following HSCT thus appears to be independent of loading conditions and could represent an improvement in intrinsic LA performance.